The Feasibility of Open Prostatectomy in Patients with History of Previous Prostate Surgery: Feasibility of Open Prostatectomy after TURP - Abedi, Amir Reza; Allameh, Farzad; Hojjati, Seyyed Ali; Ghiasy, Saleh; Pouri, Mohammad; Montazeri, Saeed (Urology Journal, 2022)
Purpose: Benign prostatic hyperplasia (BPH) is one of the most common problems in elderly men. Transurethral resection of the prostate (TURP) can be performed for most patients who need re-do prostate surgery, but open prostatectomy should be considered in patients with prostate size larger than 70 grams. This study assessed the feasibility of open prostatectomy (OP) after previous TURP in patients whose prostate size was larger than 70 grams. Materials and Methods: We subdivided patients into two groups: group 1 included patients who had a history of prostate surgery presented with severe voiding symptoms and a large prostate (>70 gram). Patients who were candidate for open simple prostatectomy without a history of prostate surgery were allocated to group 2. Results: Between June 2007 and April 2018, 2700 patients underwent TURP or open prostatectomy in our department. 152 of 2700 patients came to us because of severe voiding symptoms after previous prostate surgery, but only 30 patients met the criteria to be enrolled in this study. Perioperative complication (capsular perforation) occurred in 4 (13.3%) patients in group 1 whereas none of the patients in the group 2 had capsular perforation. Hemoglobin drop in group 1 was not significantly different from patients in group 2. The rate of blood transfusion did not differ between the groups (2 [6.6%] patients in group 1 and 41 (5.6%) patients in group 2). After 6-12 months, re-operation rate because of urethral/bladder neck stricture was done in 10 (30%) patients in group 1 and 15 (2%) patients in group 2 (p < 0.05). Four (13.3%) patients in group 1 complained of urinary leakage (more than one pad per day) 6 months after the operation whereas 5 patients in group 2 used more than one pad per day (0.7%) (p > 0.05). Hospital stay was slightly longer in patients in group 1. Six months after the operation, the patients’ quality of life was better in group 2 compared with group 1 (p < 0.05). Conclusion: Open simple prostatectomy was a feasible procedure in patients with large prostate after previous TURP, but it was associated with more complications in the long term.